A DISCOURSE ON THE METRICAL COMPOSITION OF TENYIMIA LYRICAL POETRY: FOLK POETRY - Suokhrie, Neizevonuo (International Journal of Research -GRANTHAALAYAH, 2024)
This paper presents a discourse on the metrical composition of Tenyimia Lyrical Poetry. The Tenyimia Lyrical Poetry is one of the major type among the different varieties of Tenyimia Poetry. It has a unique form of versification and metrical composition. So this paper will attempt to explore the versification and metrical system of Tenyimia Lyrical Poetry with special reference to folk poetry. Tenyimia literature has a very rich oral literature, which not only entertain but also act as an agent of preserving and transmitting cultural values, beliefs and knowledge. The lyrical poetry can also unfurl the poetic art which are aesthetically pleasing. Tenyimia literature with its elegant and classicism canons needed an exposure to the world literature. In the process of developing and exposing the Tenyimia literature, the present paper has a very significant role in unveiling the beauty and unique components and features of its metrical system with reference to the ancient folk poetry. Therefore, it is deemed vital to present and publish this paper to explore and conform the degree of our forefathers’ poetic entities as well as to empower and fortify our identity and cultural continuity. The paper shall be analytical in nature and shall adopt the qualitative research method.